Girard and the Millennials: New Perspectives on Evangelization - Sutherland, SJ, Philip (Lumen et Vita, 2014)
René Girard in conversation with Charles Taylor can help us to analyze the connection between violence and religion. Girard’s lens of mimetic desire helps to clarify how Jesus was the anti-sacrifice who desired to end the scapegoat mechanism. Taylor provides a lens on the transcendent and its sometimes hidden presence in our secular world. People are constantly feeling the cross pressures between a closed immanent frame and an openness to fulfillment outside of one’s self. Taylor’s analysis becomes concrete in the sociological research regarding Millennials and their ambivalence toward organized religion. Many young adults today are seeking the transcendent but have no idea how to find it. Additionally, they are wary of the divisiveness of religion and many view religion as but another contributor to an already violent world. However, Boeve’s image of theology as interruption gives us a lens with which to see Girard’s narrative as God’s interruption of human history. This interruption demands an equally serious, committed response. Such a demanding and meaningful narrative can be attractive to Millennials who generally view religion as simply one equally meaningless choice among others.